MONITORING DAN PENGENDALIAN KELEMBABAN, SUHU PADA TANAMAN MENGGUNAKAN METODE SISTEM IRIGASI PANCAR - Joni Warta; Achmad Noe’man; Zulkani Sinaga (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractThe growth of plants requires watering the plants so monitoring is necessary. Monitoring is carried out for the process of watering plants running optimally according to plant needs based on soil moisture and room temperature. Soil moisture explains that it settles between the soil pores, this is also due to evaporation of the soil surface, transpiration and infiltration. The purpose of this research is to do watering using a jet irrigation system so that it is done automatically in watering the soil according to the humidity and temperature required for the plants. The important factor of soil moisture is influenced by factors including the quality of the soil used as agricultural land, namely the life of the biological elements contained in the soil including hosts, pathogens, and also various other microorganisms, greatly affecting soil moisture. Determine the amount of water flow that flows from the water source to the soil element in order to get the appropriate level of humidity. In this study, the authors used cayenne pepper and red chili as the object of research, where these plants can grow at an optimal temperature of 24˚C – 28˚C, so it is necessary to monitor temperature and soil humidity using Arduino sensors to create a jet irrigation system. Keywords : Monitoring; Arduino Sensors; Water discharge; Radiant irrigation system